High-spec open-source microscopy for all. (December 2021) - Bowman, Richard; Stirling, Julian
Abstract : Open-science hardware offers unprecedented technological access to researchers and enthusiasts all over the globe. Richard Bowman and Julian Stirling of the Bath Open Instrumentation Group describe the lessons learnt in developing a low-cost, laboratory-grade microscope.